Accuracy of Caregiver-Reported Height, Weight, and BMI in a Pediatric Growth Clinic - Zhang Q; Wan NJ (Risk Management and Healthcare Policy)
Qian Zhang, Nai-Jun Wan Department of Pediatrics, Beijing Jishuitan Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Nai-Jun Wan, Department of Pediatrics, Beijing Jishuitan Hospital, Capital Medical University, 68 Huinanbei Road, Beijing, 100096, People’s Republic of China, Tel +86-010-58398102, Email wann6971@163.comObjective: To evaluate the accuracy of caregiver-reported height, weight, and body mass index (BMI) in children attending a pediatric growth clinic, and to explore the impact of these errors on clinical management and telemedicine.Methods: This cross-sectional study included 132 children aged 6– 12 years attending a pediatric growth clinic. Caregivers reported their children’s height and weight, and standard measurements were taken within one week. BMI was calculated for both sets of data. Differences between caregiver-reported and standard measurements were analyzed across gender and age. Bland-Altman and linear regression analyses assessed agreement and correlation.Results: Caregivers slightly overestimated height (+0.6 cm) and underestimated weight (− 0.9 kg), resulting in an underestimation of BMI (− 0.6 kg/m², p < 0.001). About 4.5% of overweight children were misclassified as non-overweight. Measurement errors showed no significant differences by gender or age group. Most caregivers measured their children’s height and weight approximately once per month, regardless of subgroup. Despite minor discrepancies, caregiver-reported and standard data were strongly correlated (R² > 0.9). Bland-Altman analysis revealed good agreement, though height had slightly lower concordance.Conclusion: While caregiver-reported measurements exhibited minor errors, the magnitude was comparable to previous findings in general pediatric populations. Thus, caregiver-reported data may be suitable for follow-up monitoring in pediatric growth clinics but should be used cautiously for initial diagnosis or therapeutic decisions.Keywords: caregiver-reported, measurement error, pediatric growth clinic, telemedicine